2015
DOI: 10.1080/00071668.2015.1041098
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism and expression of insulin-like growth factor 1 (IGF1) gene and its association with growth traits in chicken

Abstract: 1. The objectives of the study were to detect polymorphism in the coding region of the IGF1 gene, explore the expression profile and estimate association with growth traits in indigenous and exotic chickens. 2. A total of 12 haplotypes were found in Cornish, control layer and Aseel breeds of chicken in which the h1 haplotype was most frequent. 3. Nucleotide substitutions among haplotypes were found at 21 positions in the IGF1 gene in which 4 substitutions resulted in non-synonymous mutations in the receptor bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The regulation of IGF1 in animal growth and development has established a relationship between polymorphism and growth performance. Bian et al (2008) identified three SNPs (c.−366A>C, c.528G>A and c. * 1024C>T) that constructed haplotypes in the chicken IGF1 gene. Haplotypes based on three polymorphisms were associated with body weight traits.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of IGF1 in animal growth and development has established a relationship between polymorphism and growth performance. Bian et al (2008) identified three SNPs (c.−366A>C, c.528G>A and c. * 1024C>T) that constructed haplotypes in the chicken IGF1 gene. Haplotypes based on three polymorphisms were associated with body weight traits.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in cattle, a SNPs in the promoter region is linked with greater weight to calf weaning ( de la Rosa Reyna et al., 2010 ; Ge, Davis, Hines, Irvin & Simmen, 2001 ). In chickens and pigs some polymorphisms in the coding region are associated with growth traits ( Bhattacharya et al., 2015 ; Niu et al., 2013 ). In cashmere goats, some SNPs are linked to the wool growth ( Wu-Jun et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The SNPs within the chicken IGF1 promoter were reported by numerous previous studies [54,[86][87][88][89][90][91][92]] but according to the author's best knowledge, no research work on gene constitution of IGF1 SNP in the Hubbard F15 and Cobb E lines has been reported until now.…”
Section: Discussionmentioning
confidence: 99%